Final answer:
The force required to stretch a spring is directly proportional to the amount the spring is stretched. The force constant can be calculated using the equation F = kx. By substituting the given values into the equation, we can find the unknown weight W.
Step-by-step explanation:
The force required to stretch a spring is directly proportional to the amount the spring is stretched. This can be represented by the equation F = kx, where F is the force, k is the force constant, and x is the amount the spring is stretched. In this scenario, we are given that a 19 N weight stretches the spring by 33 m at equilibrium.
To find the force constant, we can use the equation:
k = F / x = 19 N / 33 m = 0.58 N/m
Next, we need to find the unknown weight W that will stretch the spring to a new equilibrium position 17 m below the position with no weight attached. Using the force constant we calculated, we can use the equation F = kx to find the force required:
F = kx = (0.58 N/m)(17 m) = 9.86 N
Therefore, the unknown weight W that will stretch the spring to the new equilibrium position is 9.86 N.